Socio-economic Characteristics and Land Allocation on Tidal Swampland Agriculture in Indonesia - Kurniawan, Ahmad Yousuf; Justus Liebig University Giessen (My University, 2024)
Indonesia, as the world’s fourth most populous country after China, India and the USA, has higher susceptibility to food supply, especially rice. Rice production is not sufficient to cover the local demand. Furthermore, the population continues to increase while the rice productivity tends stagnate. Kalimantan Island has a large scale of tidal swampland rice farming. Swampland across Kalimantan has varied characteristics. Rice fields in the tidal swampland area are vulnerable to flooding, pest attacks, and seawater intrusion. The effects are predicted not only on production, but also on farmers’ income and other social-economic aspects. This research aims to describe the socio-economic characteristics of swampland area, determine a model of farmer households which has optimum gross margin under restricted resources in the tidal swampland, and simulate the fluctuation of gross margin as the result of crops price fluctuation in the tidal swampland area of South Kalimantan, Indonesia. The modelling based on linear programming was formulated to assess land allocation across three typologies of tidal swampland with the gross margin as the objective function. The tidal swampland typologies observed were type A (directly affected by tidal movement and always floods), type B (directly affected by tidal movement but only floods during the spring tide) and type C (indirectly influenced by the tidal movement). This research found that the socio-economic characteristics of farmers in tidal swampland areas in South Kalimantan, Indonesia, are different based on the swampland typology. It was found that farmers in all typologies allocated their land for rice farming exceeding the values suggested by the model. On the other hand, they allocated land for perennial crops below the model values, especially on type C and even more on type A. As the results, the farmers in all typologies of tidal swampland obtained lower gross margin than the optimum value that resulted from the model. This result suggests that the farmers could optimize their gross margin. There are two ways to increase the gross margin. First, for the main crops (local and HYV rice), the farmers should increase their land productivity through intensive farming. Secondly, for the perennial crops (coconut and orange), the farmers could optimize their production by expanding the area used to cultivate them. Because the perennial crops are more suitable in the swampland environment.
Keywords: swampland agriculture; farming practice; socio-economic characteristic; land allocation; linear programming; household model; price volatility; ddc:300; ddc:330; ddc:630